1998
DOI: 10.1021/ef970183j
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Water Sorbed in Coal on the Basis of Congelation Characteristics

Abstract: Water sorbed in eight coals of different ranks was analyzed by differential scanning calorimetry (DSC) over a temperature range from 123 to 293 K. On the basis of its congelation characteristics, the water was classified into three types: free water that is identical with bulk water, bound water that freezes at a lower temperature than free water, and nonfreezable water that never freezes in the present temperature range. The contents of the free and bound waters were experimentally determined from their respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 29 publications
4
82
0
Order By: Relevance
“…Presence of cations can also influence swelling of lignite in water (Allardice et al 2003). Norinaga et al (1998) found three types of water in coals of different ranks and reported also on molecular modeling results confirming expansioncontraction conformational transitions of coal molecules in response to the change in the number of water molecules. Suuberg et al (1993) published evidences that in addition water can affect diffusion processes within the lignite structure.…”
Section: Resultsmentioning
confidence: 78%
“…Presence of cations can also influence swelling of lignite in water (Allardice et al 2003). Norinaga et al (1998) found three types of water in coals of different ranks and reported also on molecular modeling results confirming expansioncontraction conformational transitions of coal molecules in response to the change in the number of water molecules. Suuberg et al (1993) published evidences that in addition water can affect diffusion processes within the lignite structure.…”
Section: Resultsmentioning
confidence: 78%
“…The plot for the m/z 18 ion shows an initial peak extending from approximately 85 to 225°C (apex at 125°C) that can be assigned to the drying of "sorbed" water. In this context, sorbed water is defined as the free (bulk), bound, and nonfreezable water described by Noringa et al 21,22 A second peak beginning at approximately 340°C whose apex is at approximately 500°C can be assigned to chemically formed pyrolytic water observed by other researchers. 1,20 Similar sorbed water drying peaks are observed in the m/z 20 trace (D 2 O) and m/z 19 (HDO) trace.…”
Section: Effect Of the Lignite:deuterium-labeled Water Ratiomentioning
confidence: 99%
“…This topic has been extensively studied in soil research and sludge dewatering. There are a number of interpretations available on the types of water associated with soil, sludge, and coal [7][8][9][10][11][12].…”
Section: Forms Of Watermentioning
confidence: 99%